Openness, financial markets, and policies: Cross-country and dynamic patterns - Giuseppe Bertola; Anna Lo Prete (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
We document significant and robust empirical relationships in cross-country panel data between government size or social expenditure on the one hand, and trade and financial development indicators on the other. Across countries, deeper economic integration is associated with more intense government redistribution, but more developed financial markets weaken that relationship. Over time, controlling for country-specific effects, public social expenditure appears to be eroded by globalization trends where financial market development can more easily substitute for it.
urn:nbn:de:hebis:30-62348
Keywords: F4; 330; Financial Development; Globalization; Social Policy; Globalisierung; Offene Volkswirtschaft; Wirtschaftsintegration; Sozialpolitik; Kapitalmarktliberalisierung; Arbeitsmarktpolitik; Welt